EDUCATIONAL EFFICIENCY AND QUALITY ISSUES IN THE CONTEXT OF DIGITALIZATION OF THE EDUCATIONAL PROCESS (Universal International Scientific Journal, 2026)
This article provides a scientific and methodological analysis of the issues of ensuring the efficiency and quality of education in the context of digitalization of the educational process. The impact of the introduction of modern information and communication technologies into the education system on the organization of the educational process, the level of knowledge acquisition, and the effectiveness of educational results is highlighted.
Keywords: digital technologies, digitalization of the educational process, quality of education, educational efficiency, information and communication technologies, digital learning environment, distance learning, e-learning resources, pedagogical innovations, digital competence.